ФАКТОРЫ ПОВЫШЕНИЯ КОНКУРЕНТОСПОСОБНОСТИ НАЦИОНАЛЬНЫХ КАДРОВ - C. A. Kaliyeva; M. K. Meldakhanova (Экономика: стратегия и практика, 2018)
In this article, the main factors affecting the competitiveness of national personnel are reviewed and systematized. Particular attention is paid to the qualitative parameters of competitiveness of young specialists. The main problems affecting the improvement of the quality of personnel training are revealed.